2008
DOI: 10.1902/jop.2008.070203
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1 Gene Polymorphism, Diabetes, and Periodontitis: Results From the Study of Health in Pomerania (SHIP)

Abstract: Subjects with type 2 diabetes have an increased risk for periodontitis, which is aggravated further if combined with the variant IL-1A/1B genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 25 publications
(31 reference statements)
0
20
2
2
Order By: Relevance
“…To date, only a few studies have been made to investigate whether gene polymorphisms of certain cytokine genes are associated with periodontal disease in diabetic patients. A recent crosssectional study (Struch et al 2008) reported an increase in the severity of periodontal disease along with increasing levels of HbA1c among type 2 diabetic subjects and further, there was a significant association between T-bearing risk genotype of IL-1A/1B and periodontal disease in diabetic but not in non-diabetic subjects. Another study (Guzman et al 2003) also found a trend suggesting that allele 1 at IL-1B was over-represented among diabetic subjects with periodontal disease.…”
Section: Discussionmentioning
confidence: 88%
“…To date, only a few studies have been made to investigate whether gene polymorphisms of certain cytokine genes are associated with periodontal disease in diabetic patients. A recent crosssectional study (Struch et al 2008) reported an increase in the severity of periodontal disease along with increasing levels of HbA1c among type 2 diabetic subjects and further, there was a significant association between T-bearing risk genotype of IL-1A/1B and periodontal disease in diabetic but not in non-diabetic subjects. Another study (Guzman et al 2003) also found a trend suggesting that allele 1 at IL-1B was over-represented among diabetic subjects with periodontal disease.…”
Section: Discussionmentioning
confidence: 88%
“…However, the study did not indicate the type of diabetes, and the stratification of genotype associations by ethnicity resulted in small groups of patients, making it difficult to interpret the results. Another study, 40 conducted in a German population, found that the IL‐1 −511 CT or TT genotypes were significantly associated with periodontitis in patients with diabetes but not in patients without diabetes. This result is at variance with our results, suggesting that the TT genotype is a protective factor for periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies 39,40 addressing a possible genetic association between periodontitis and type 2 diabetes have been published. One study 39 found that the IL‐1B −511 C allele was significantly associated with periodontitis in a subset of African American patients with diabetes (n = 29).…”
Section: Discussionmentioning
confidence: 99%
“…While periodontitis may be a risk factor for development or deterioration of type 2 diabetes, type 2 diabetes may also be a risk factor for the development of periodontitis. Patients with type 2 diabetes suffer from periodontitis more often and more severely than non-diabetics (Emrich et al 1991, Collin et al 1998, Tsai et al 2002, Campus et al 2005, De Silva et al 2006, Struch et al 2008. Hence, there may be a bilateral causal relationship between periodontitis and type 2 diabetes, with one influencing the other and vice versa.…”
mentioning
confidence: 99%